Symmetrization and sharp Sobolev inequalities in metric spaces - Milman, Mario; Kališ, Jan (Revista Matemática Complutense, 2009)
We derive sharp Sob olev inequalities for Sob olev spaces on metric spaces. In particular, we obtain new sharp Sob olev emb eddings and Fab er-Krahn estimates for H¨rmander vector fields. o